2014
DOI: 10.1097/ijg.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A Protects RGC-5 Cells From Excitotoxic Cell Death

Abstract: CSA can effectively protect RGC-5 cells against glutamate-induced excitotoxicity. Therefore, CSA should be tested in further experiments to evaluate its potential as a neuroprotective substance against RGC disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…In summary, 9 µg/mL CsA presented good biocompatibility and induced a neuroprotective effect after hypoxic treatment. The observed neuroprotective effect is in line with the previously published data [ 25 , 26 ]. Thus, CsA might have additional therapeutic potential in the treatment of glaucoma or ischemic retinal vascular diseases like diabetic retinopathy or retinal vein occlusion.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In summary, 9 µg/mL CsA presented good biocompatibility and induced a neuroprotective effect after hypoxic treatment. The observed neuroprotective effect is in line with the previously published data [ 25 , 26 ]. Thus, CsA might have additional therapeutic potential in the treatment of glaucoma or ischemic retinal vascular diseases like diabetic retinopathy or retinal vein occlusion.…”
Section: Discussionsupporting
confidence: 93%
“…In retinal hypoxia after intraocular pressure elevation, CsA also proved to be a potent neuroprotective agent [ 25 ]. In this work, concentrations of 1, 3, 6, and 9 µg/mL were chosen since higher concentrations induced a decrease in cell viability in a previously published study using RGC-5 cells [ 26 ]. In a study by Kaminska et al, slightly higher concentrations (8–40 µM) led to the apoptosis of mixed neuronal/glial cultures, where TUNEL + staining was observed only in neurons while astrocytes were unaffected [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schultheiss et al 20 demonstrated that cyclosporine has a dose-dependent neuroprotective effect that enhances the survival of rat ganglion cells in culture when cyclosporine concentrations exceed 1 lg/mL. The minipigs used for our study had been under cyclosporine treatment; however, we found that the spread of ganglion cell activity was equally large in the retinas of sham-treated pigs (no cyclosporine, data points to the left of the dashed vertical line in Fig.…”
Section: Long Retinal Ganglion Cell Survival By Slow Cooling To 48ccontrasting
confidence: 48%